Climate Change: Assessing the Vulnerability of the Niger Delta Region, in Nigeria - Stephena Udinmade Ighedosa (Modern Advances in Geography, Environment and Earth Sciences Vol. 3, 2021)
Climate change includes both the global warming phenomenon, driven by greenhouse-emitting anthropogenic activities and the associated large scale shift in weather patterns. Climate change is not just a global threat, but an unprecedented public health emergency. Climate change has been characterized by global warming, increased frequency and intensity of precipitation, catastrophic wind events, and extreme weather events, associated with heat waves, flooding disasters, and prolonged droughts. The United Nations Framework Convention on Climate Change (UNFCCC) has prescribed abatement agreements, based on precautionary principle and principle of cost and responsibility, amongst member nations to reduce greenhouse gas emissions. Globally, the most vulnerable regions, to hazardous impacts of climate change, are the mega-deltas of Africa and Asia, due to high exposure to sea level rise, storm surges, coastal erosion and river flooding, compounded by increasing human-induced pressures on coastal areas. The vulnerability of the Niger Delta region is exacerbated by oil spillages, gas flaring and environmental degradation. This chapter draws attention to the vulnerability of the Niger Delta to the adverse impact of climate change and the urgency of the implementation of mitigation and adaptation as opportunities for full transformation of economies, of the Niger delta region, in line with sustainable developmental goals (SDGs).